Midazolam e remifentanil versus propofol e remifentanil para intubaçãotraqueal em recém-nascidos pré-termos com síndrome do desconforto respiratório - Marcia Gomes Penido Machado (2010)
Objective: the aim of this study was to compare the intubation conditions following the use of either propofol or midazolam in combination to remifentanil as premedication for tracheal intubation in premature neonates with respiratory distress syndrome (RDS). Method: a double blind, randomized, controlled trial was performed. Interventions and patients: 20 preterm neonates (28-34 wk) admitted to two tertiary NICUs with RDS, were submitted to tracheal intubation following the use of remifentanil associated to either propofol (n=10) or midazolam(n=10) as premedication. The Ethics Committee of both institutions has approved the study and an informed consent was obtained from the parents of all selected subjects. Main outcome measures: intubation conditions were scored based on a four-point scale according to: the ease of laryngoscopy, position of vocal cords, coughing, jaw relaxation, and movement of the limbs. Results: considering the specific intubations conditions according to the score used, there were no statistical differences among the parameters valuated. According to our findingsthere are no differences in the quality or difficulty of intubation; in the presence of adverse effects; in the hemodynamic variables and in the quality of sedation and analgesia achieved when midazolam or propofol are used as hypnotic associated to remifentanil as premedication for tracheal intubation in premature neonates (28- 34 weeks gestation). Conclusion: besides midazolam, propofol might be a validalternative as hypnotic drug to the regimen of premedication for endotracheal intubation in neonates. Further RCT enrolling different centers are warranted to confirm our preliminary data.